Comparison of clinical variables and outcome of 2 natural equine herpesvirus myeloencephalopathy outbreaks induced by equine herpesvirus‐1 A2254/N752 strain in sport horses - María de laCuesta‐Torrado; Ana Velloso Alvarez; José Miguel Cárdenas‐Rebollo; Patricia Neira‐Egea; Valentina Vitale; Juan Cuervo‐Arango (Journal of Veterinary Internal Medicine)
Abstract Background Understanding of equine herpesvirus‐1 (EHV‐1) myeloencephalopathy (EHM) is complicated by disparities among studies. Objective Compare clinical findings and outcome in horses involved in 2 recent EHM outbreaks. Animals Twenty‐five and 10 horses affected during 2 natural EHM outbreaks were admitted to a veterinary teaching hospital (VTH) in 2021 and 2023, respectively. Methods Data collected from the VTH and surveys completed by riders and horse owners were analyzed retrospectively. Results No risk factors associated with EHM development showed significant differences between the outbreaks; both outbreaks were caused by A2254/N752 strains. Treatments administered for EHM were not significantly different, whereas the duration was longer in 2021 for flunixin meglumine (P = .01) and dimethyl sulfoxide (P < .001). In 2021, more horses required hospitalization (P = .02), and fatality rate was 32%, whereas in 2023, no patient died. Hospitalization duration was longer in 2021 than in 2023 (P = .06) and 11.7% of horses from 2021 returned to competition within 6 months, whereas 100% in 2023 did (P < .001). Ataxia grade upon admission was equivalent in 2021 and 2023, but factors related to poor prognosis, such as simultaneous development of urinary and vascular complications, occurred in 2021 but not in 2023 (P = .01). Conclusions and Clinical Importance Two EHM outbreaks caused by the A2254/N752 strain differed in disease severity. Urinary complications and systemic signs of vasculitis were important clinical variables associated with prognosis. Systemic complications in horses with EHM lead to a worse prognosis.